2001
DOI: 10.1097/00005392-200104000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Unilateral Urolithiasis With Sleep Posture

Abstract: Although the exact pathophysiology of the association between sleep posture and recurrent unilateral stone disease remains to be elucidated, sleep posture may alter renal hemodynamics during sleep and promote stone formation. This observation needs further investigation and should be factored into the evaluation and prevention of unilateral urinary stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…Renal flow studies have found increased blood flow to the dependent kidney when patients are positioned in a lateral decubitus position for at least 30 min. This hemodynamic difference leading to increased blood flow to the dependent kidney may result in hyperfiltration and may be partially responsible for stone formation [23].…”
mentioning
confidence: 99%
“…Renal flow studies have found increased blood flow to the dependent kidney when patients are positioned in a lateral decubitus position for at least 30 min. This hemodynamic difference leading to increased blood flow to the dependent kidney may result in hyperfiltration and may be partially responsible for stone formation [23].…”
mentioning
confidence: 99%
“…11 Apesar de não existir na literatura um consenso sobre a lateralidade do cálculo, há relatos de que o lado mais acometido no homem é o esquerdo e, na mulher, o direito. 2 Shekarriz et al 15 postularam que existe uma ligação entre a lateralidade do cálculo e o lado sobre o qual o paciente tem o hábito de dormir.…”
Section: Resultsunclassified
“…4,5,7,9 Yet to date, no data exists comparing excretory renal function between patients with unilateral and bilateral stone disease. The lungs provide and ideal example of a paired organ system where variations in anatomy, position, and perfusion have profound effects on mate pulmonary function and underlying pathology.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some have surmised that differences in renal perfusion or anatomy have led to such observations. 4,5 …”
Section: Introductionmentioning
confidence: 99%